2014
DOI: 10.1186/2036-7902-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital stroke diagnostics based on neurological examination and transcranial ultrasound

Abstract: BackgroundTranscranial color-coded sonography (TCCS) has proved to be a fast and reliable tool for the detection of middle cerebral artery (MCA) occlusions in a hospital setting. In this feasibility study on prehospital sonography, our aim was to investigate the accuracy of TCCS for neurovascular emergency diagnostics when performed in a prehospital setting using mobile ultrasound equipment as part of a neurological examination.MethodsFollowing a ‘911 stroke code’ call, stroke neurologists experienced in TCCS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 47 publications
0
44
0
4
Order By: Relevance
“…Two papers excluded patients aged under 16 years. Three used paediatric samples , one investigated patients aged over 65 years and one excluded patients whose initial clinical examination showed no sign of stroke .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers excluded patients aged under 16 years. Three used paediatric samples , one investigated patients aged over 65 years and one excluded patients whose initial clinical examination showed no sign of stroke .…”
Section: Resultsmentioning
confidence: 99%
“…The average sample size was 742 (SD, 1236.78; range, 20 [27]8187 [28] [27,31,32], one investigated patients aged over 65 years [33] and one excluded patients whose initial clinical examination showed no sign of stroke [34].…”
Section: Study Samples and Settingsmentioning
confidence: 99%
“…This modality can diagnose middle cerebral artery (MCA) occlusion with a reasonably high degree of accuracy. In one German study, transcranial ultrasound used in a prehospital setting demonstrated a sensitivity of 78% and specificity of 98% for the diagnosis of MCA or internal carotid artery occlusion in comparison with CTA/MRA performed at receiving hospitals 74. In addition, investigations are continuing into the use of ultrasound, with or without microbubble contrast administration, to assist in mechanical clot dissolution or aid the cerebral microcirculation, potentially providing some degree of prehospital clot ‘conditioning’ or neuroprotection before definitive treatment 73.…”
Section: Prehospital Efficiency Opportunities In Elvo Strokementioning
confidence: 99%
“…Future challenges of UPI in acute stroke should focus on multicenter validation of up-to-date study results as well as the potential of mobile application. First attempts of mobile cerebral ultrasound imaging in acute stroke have focused on vessel imaging [24], but also basic perfusion imaging is challenged in one industrial project [25]. In addition to being a bedside method, UPI may also be used for serial studies in order to follow-up on brain perfusion.…”
Section: Clinical Applications Up To Date and Future Indicationsmentioning
confidence: 99%